Integration of Heat Pumps in Social Housing—Role of User Behaviour and User Satisfaction - Shilpi Tewari; Priyadarsini Rajagopalan (Buildings)
Many countries around the world have rolled out energy efficiency programs and incentives to encourage the adoption of energy-efficient technologies, including heat pumps. Currently, the academic investigation of heat pump technology implementation in Australia, particularly within the social housing sector, is quite sparse. This knowledge gap is particularly evident in the realm of comprehending user acceptance related to comfort, operating and capital costs, and the ability to operate and the extent to which occupants in social housing embrace and adapt to this technological advancement. This paper aims to systematically review studies that have surveyed users and other stakeholders involved in the heat pump ecosystem within the social housing setting. The key objective is to investigate the impact of heat pump installation in social housing on tenant well-being, focusing on the reduction of energy costs, improvements in indoor comfort, and tenant perceptions of financial and social barriers. By analysing 69 studies, this paper identifies the critical challenges and opportunities in integrating heat pump systems into social housing. The key findings emphasise that tenant education, effective communication, and engagement are essential for maximising the benefits of heat pumps. Furthermore, the financial feasibility of heat pumps depends on government incentives and careful system design to avoid excessive upfront and operational costs. This review offers a comprehensive guide for future research and policy development, aiming to facilitate the integration of heat pumps in social housing, with a focus on improving tenant well-being and reducing energy poverty.